Calculation of the exposure buildup factors for x-ray photons with continuous energy spectrum using Monte Carlo code. (22nd January 2018) - Rafiei, Mustafa Mohammad; Tavakoli-Anbaran, Hossein
Abstract: Exposure buildup factors are very important for the calculation of radiation shielding and also applied radiation. We must distinguish the monoenergetic and continuous energy spectrum gamma source in order to calculate the exposure buildup factors. In this study, the exposure buildup factors for two x-ray continuous energy spectra (bremsstrahlung) with 5 and 10 MeV endpoint energies were calculated up to depths of 10 mfp of water. It was observed that there is a large difference between the obtained exposure buildup factors due to the monoenergetic and continuous energy spectrum gamma sources. The calculation results show that the relative differences in 5 MeV energy for 1 mfp to 10 mfp are 114% to 44%, respectively, and also the relative differences in 10 MeV energy for 1 mfp to 10 mfp are 87% to 38%, respectively. Actually, the main purpose of this paper is to illustrate the fact that there is a significant difference between the exposure buildup factors due to the continuous and monoenergetic gamma sources. Therefore, radiation staff must pay more attention to calculating the thickness of radiation shields for continuous energy gamma sources.